Mumpreneurs? : everyday complexities in the realm of time, money, business and motherhood - Luomala, Katri (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2018)
This study analyses the complexity of everyday life choices and constraints of women who are mothers and work as entrepreneurs. The research illustrates how women construct their motherhood and entrepreneurship as a part of their everyday lives and examines the constructions that shape their life choices. Multiple interpretations of work, an aim towards work-life balance and the increasingly entrepreneurial nature of work all come together in the concept of mumpreneur, a portmanteau of mother and entrepreneur, which has been created as a distinction from the traditional masculine label. In traditional entrepreneurship literature, parenthood is mainly ignored, and even in research of women’s entrepreneurship family is easily constructed as problematic. This study, for its part, aims to bring the fields of entrepreneurship and motherhood closer together by further conceptualizing mumpreneurship through empirical research and by opening up new discussions in the fairly narrow research field of self-employed mothers. In the empirical part of the study, the analysed data comprises a focus group discussion between three self-employed mothers and individual interviews with four self-employed mothers. The study adopts moderate constructionism and applies an abductive approach in the analysis in order to develop the concepts of time, money, business and motherhood within the field of mumpreneurship research. This study contributes to research on mumpreneurship and the work-family interface by revealing the diversity of the life choices and constraints of women in a similar life phase and by questioning the use of the stabilising label of mumpreneur, which only reinforces the traditional gendered division of work within families. This study also contributes to the field of mumpreneurship by expanding the concept itself. Mumpreneurship started with the traditional male entrepreneur’s model as its foundation and was further developed through the introduction of spatial dimensions and the question of combining childcare and paid work. This study further conceptualises mumpreneurship as a way to do paid work where the ambivalence of motherhood and professional ambitions are tied into one’s everyday life within the realm of needing to make a living out of one’s business. Self-employed mothers, in the Finnish context, do not experience entrepreneurship as analogous with the choice between being a stay-at-home mother and a working mother, instead, entrepreneurship is constructed as the choice of an active working citizen. However, this active choice does not guarantee a better standard of living, as the income derived from it is often insecure and modest. The shortcomings in income are compensated with the spouse’s income, whereas the shortcomings in time-use are compensated with a more complex combination of intergenerational help, outsourcing domestic chores, balancing time-use with the spouse and one’s own flexibility in organising everyday life.

Tämä tutkimus analysoi arkielämän valintoja ja rajoitteita sellaisten naisten elämässä, jotka ovat äitejä ja työskentelevät yrittäjänä. Työssä tarkastellaan sitä, kuinka naiset rakentavat äitiyttään ja yrittäjyyttään osana arkielämäänsä ja millaiset tulkinnat muovaavat heidän valintojaan. Työn monet merkitykset, pyrkimys työn ja muun elämän tasapainoon sekä työn muuttuminen entistä yrittäjämäisemmäksi kohtaavat käsitteessä mumpreneur, joka on yhdistelmä sanoista mother ja entrepreneur, äiti ja yrittäjä. Tämä äiti-yrittäjän käsite on kehitetty erotuksena perinteisestä, maskuliinisesta yrittäjästä. Vanhemmuutta ei ole käsitelty perinteisessä yrittäjyyskirjallisuudessa, ja jopa naisyrittäjyystutkimuksessa perhe konstruoidaan helposti ongelmaksi. Tämä tutkimus pyrkii osaltaan tuomaan yhteen yrittäjyyden ja äitiyden tutkimuskenttiä käsitteellistämällä äiti-yrittäjyyttä empiiristä tutkimusta hyödyntämällä ja tuomalla esiin uusia keskustelunaiheita yrittäjänä toimivien äitien arkielämästä. Tutkimuksen empiirinen aineisto koostuu kolmen yrittäjänä toimivan äidin fokusryhmäkeskustelusta ja neljän äiti-yrittäjän yksilöhaastatteluista. Tutkimus on otteeltaan maltillisen konstruktionistinen ja hyödyntää analyysissa abduktiivista lähestymistapaa tehdäkseen uusia avauksia äiti-yrittäjyyskeskusteluun koskien aikaa, rahaa, liiketoimintaa ja äitiyttä. Tutkimus tekee näkyväksi näennäisesti samankaltaisessa elämänvaiheessa olevien naisten valintojen ja rajoitteiden moninaisuutta ja kyseenalaistaa stabilisoivan ja perinteistä sukupuolittunutta työnjakoa vahvistavan mumpreneur-käsitteen käyttöä. Samalla tutkimus laajentaa mumpreneur-käsitettä. Äiti-yrittäjyys on lähtenyt perinteisestä miehisen yrittäjyyden mallista, laajentunut käsittelemään tilallisia ulottuvuuksia ja kytkeytynyt lastenhoidon ja ansiotyön yhdistämisen keskusteluun. Tämä tutkimus osaltaan käsitteellistää äiti-yrittäjyyttä ansiotyön muotona, jossa äitiyden ja ammatillisen kunnianhimon väliset ristiriitaisuudet kytkeytyvät arkielämän tarpeeseen ansaita elantonsa liiketoiminnalla. Äideillä yrittäjänä toimiminen ei suomalaisessa kontekstissa vertaudu valintaan kotiäidin ja työssäkäyvän äidin roolien välillä, vaan rakentuu pikemminkin aktiivisen työssäkäyvän kansalaisen valinnaksi. Tämä aktiivinen valinta ei kuitenkaan takaa parempaa elintasoa, koska ansiot ovat epävarmoja ja monesti melko vaatimattomia. Ansiotason riittämättömyyttä pystytään kompensoimaan puolison tuloilla, kun taas ajan riittämättömyyttä kompensoidaan monimutkaisemmalla yhdistelmällä sukupolvien välistä apua, teettämällä kotityötä ostopalveluina, tasapainottamalla ajankäyttöä puolison kanssa ja kykenemällä itse joustavuuteen arjessaan.